2017
DOI: 10.1007/s00125-017-4410-4
|View full text |Cite
|
Sign up to set email alerts
|

Live attenuated enterovirus vaccine (OPV) is not associated with islet autoimmunity in children with genetic susceptibility to type 1 diabetes: prospective cohort study

Abstract: Aims/hypothesis Animal and human studies have implied that enterovirus infections may modulate the risk of islet autoimmunity and type 1 diabetes. We set out to assess whether serial administration of live oral poliovirus vaccine (OPV) in early life can influence the initiation of islet autoimmunity in a cohort of genetically predisposed children. Methods OPV was administered to 64 children and a further 251 children received inactivated poliovirus vaccine (IPV). The emergence of type 1 diabetes-associated aut… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
4
0
1

Year Published

2018
2018
2023
2023

Publication Types

Select...
5

Relationship

1
4

Authors

Journals

citations
Cited by 5 publications
(5 citation statements)
references
References 29 publications
0
4
0
1
Order By: Relevance
“…28 29 Administration of oral poliovirus vaccine may increase the detection of enterovirus in stool samples, but this cohort received inactivated poliovirus vaccine injections. 30 31…”
Section: Discussionmentioning
confidence: 99%
“…28 29 Administration of oral poliovirus vaccine may increase the detection of enterovirus in stool samples, but this cohort received inactivated poliovirus vaccine injections. 30 31…”
Section: Discussionmentioning
confidence: 99%
“…Enterovirus appears to occur year-round with higher prevalence in late spring throughout early autumn [ 20 ]. Besides, the high rate of enterovirus detection might be due to the administration of live oral poliovirus vaccine (OPV) that caused increased enterovirus detected in stool samples [ 21 ].…”
Section: Discussionmentioning
confidence: 99%
“…Previous studies have suggested that such epitopes may exist, but their role in the pathogenesis of T1D remains elusive [116]. A clinical vaccine candidate should ideally avoid these epitopes, even if the inactivated CVB vaccine does not exaggerate the development of diabetes in NOD mouse [107], and there are no indications that polio vaccines could cause diabetes, even when children with increased genetic susceptibility to T1D were vaccinated [117]. In addition, maternal antibodies against CVBs in cord blood do not increase the risk of T1D in the child arguing against the role of antibody mediated cross-reactivity [76].…”
Section: Preclinical Development Of a Cvb Vaccine Against T1dmentioning
confidence: 99%